The portrayal of womanin Arab contemporary feminine literature - LAREK, RYM (My University, 2017)
The reader of Arab feminine literature can observe the progress that the field is witnessing since last decade. Indeed, contemporary literary works try to follow the political and social events, in order to reflect reality through fictional stories and characters. With regard to the portrayal of woman in Arab feminine literary works, I chose to analyse feminine major characters in two dissimilar novels:“The Black Suits You Well” (2012) of Ahlem Mostghanemi and “The Map Of Love” (1999) of Ahdef Soueif ; Using qualitative research method to find out the manner the protagonists are demonstrated, which is inspired from the different views of the two writers toward woman situation and identity. Mostghanemi displays the brave woman challenging difficulties in her social life, but she is totally manipulated and exploited emotionally in her love affair. On the other hand, Ahdef Soueif exposes a different woman model, who is aware of her identity and her inner capacities, she is a good partner who supports her husband and works with him equally to succeed their life. Thus, these two studies drove to observe an example of women seeking to perform their feminine identity in a successful version, which is through their roles and reactions to life events.
in The Black Suits You Well (2012) Ahlem Mosteghanemi and The Map Of Love (1999) Ahdef Soueif
Keywords: Feminine literature; Ahlem Mosteghanemi, Black Suits You Well (2012); Ahdef Soueif, Map Of Love (1999); patriarchial society; feminine identity; Successful women